Anatomy, Clinical Significance, and Management of Struthers’ Ligament: A Comprehensive Review - Rajani Singh (Medical Science: Recent Advances and Applications Vol. 5, 2025)
The Struthers’ ligament in most cases, connects the supracondylar process of the humerus and the medial epicondyle of the humerus. The median nerve and the brachial artery pass deep to this ligament, compressing these neurovascular bundles, creating ischemic and neural alterations. Besides the Struthers’ ligament, there are other reasons for the compression of the median nerve which should be excluded. But there are reports that though the Struthers’ ligament is present it still does not cause compressive neuropathy of the median nerve. Moreover, though classically the Struthers’ ligament is reported to connect the supracondylar process of the humerus and medial epicondyle of the humerus but there are cases where the Struthers’ ligament is observed in the absence of the supracondylar process of the humerus. The compressive neuropathy caused by the Struthers’ ligament is managed by surgical excision of this ligament. Thus, the aim of the chapter is to highlight the anatomy of the Struthers’ ligament, causes and clinical implications caused by it and treatment to relieve neuropathy caused by the Struthers’ ligament. So, the literature was explored using various databases like PubMed, Google Scholar, Scielo, Medline, etc. Knowledge of the varied anatomy of Struthers’ ligament will be of paramount importance in treating neuropathies caused by compression of structures passing deep to Struthers’ ligament.